Understanding the dimensions of intensive care: transpersonal caring and complexity theories (Revista Latino-Americana de Enfermagem, 2009)
This is a descriptive, interpretive and qualitative study carried out at the ICU of a Brazilian teaching hospital. It aimed to understand the dimensions of human caring experienced by health care professionals, clients and their family members at an ICU, based on human caring complexity. The Transpersonal Caring and Complexity theories support theory and data analysis. The following dimensions of care emerged from the themes analyzed according to Ricoeur: self-care, care as an individual value, professional vs. informal care, care as supportive relationship, affective care, humanized care, care as act/attitude, care practice; educative care, dialogical relationship, care coupled to technology, loving care, interactive care, non-care, care ambience, the essence of life and profession, and meaning/purpose of care. We believe in care that encompasses several dimensions presented here, based on the relationship with the other, on the empathetic, sensitive, affectionate, creative, dynamic and understanding being in the totality of the human being.